Anthracological and Carpological Perspectives on Settlement, Cultivation and Woodland Management in England, c. AD 450-1100 - Francis, Robert (2022)
This thesis examines the archaeobotanical evidence for settlement, cultivation, and woodland management in England during the early medieval period, here defined as the era between the 5th and 11th centuries AD. The research provides new perspectives on how the landscape and woodlands were managed for fuel and building materials and provides evidence of horticultural cultivation of food, craft, and medicinal plants. A multidisciplinary approach is taken combining carpological and anthracological analysis of primary archaeological material using the evidence from the settlements at Dando Close, Higham Ferrers and Flixborough in the East Midlands of England as principal case studies. This was supported by the creation of an extensive comparative data collection study of archaeobotanical records from early medieval Britain, as a whole. This research also provides the first application of a quantitative dendro-anthracological approach to English sites, exploring patterns of oak use in early medieval England. The outcomes of the dendro-anthracological study have yielded ground-breaking high-resolution evidence of timber and fuel wood collection strategies and woodland management regimes. The exceptionally well-preserved charcoal from the early medieval settlement of Flixborough has allowed a unique insight into the selection of timber for the renovation of buildings and possible long-term woodland management strategies undertaken in the area during the mid 8th to 9th century AD. To further support the research into horticulture and woodland management an experimental early medieval rural garden was created, with the purpose of providing essential experimental data to compliment the analytical research and to allow observations of the plants’ growth habit as well as providing material to conduct reference analysis for the methodology and interpretation. The garden also functioned as an open-air laboratory for public engagement and outreach activities that were supported by a range of hands-on STEAM (science, technology, engineering, art, and maths) laboratory workshops. To help contextualise the archaeobotanical evidence, selected medieval textual sources are assessed, to explore documented horticultural and silvicultural strategies from the early medieval period, as well as the uses of wild and domestic plants for medicine.